Effect of tibolone on the survival of early stage cervical adenocarcinoma patients - Seung-Ho Lee; Yoon-Jin Cho; Kyung-Joo Cho; Mee-Hyang Ko; Sun-Young Jung; Seung-Joo Chon; So-Yi Lim; Kwang-Beom Lee (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveGynecologic oncologists are uncertain about the safety of tibolone application in cervical adenocarcinoma (AC) patients. This study examined the possible adverse effects of tibolone on the survival of cervical AC patients.MethodsMedical records of 70 cervical AC patients with International Federation of Gynecology and Obstetrics stages IA to IB were reviewed. A bilateral salpingo-oophorectomy was performed in all patients, and survival outcomes between tibolone users (n=38) and non-users (n=32) were compared.ResultsA comparison of the tibolone users with non-users revealed similar clinicopathological variables. Progression-free survival (P=0.34) and overall survival (P=0.22) were similar in the users and non-users. The risks of progression (hazard ratio [HR], 1.71; 95% confidence interval [CI], 0.46-6.37; P=0.43) and death (HR, 1.59; 95% CI, 0.06-45.66; P=0.79) were also similar in both groups.ConclusionTibolone has no adverse effect on the survival of cervical AC patients and can be administered safely to this population. These findings may be helpful in improving the quality of life of cervical AC patients.